On the effect of boron on grain boundary character in a new polycrystalline superalloy. (15th January 2016) - Kontis, P.; Yusof, H.A. Mohd; Pedrazzini, S.; Danaie, M.; Moore, K.L.; Bagot, P.A.J.; Moody, M.P.; Grovenor, C.R.M.; Reed, R.C.
Abstract: The role of boron in conferring the grain boundary character in a new polycrystalline superalloy suitable for power generation applications is considered. One boron-free and three boron-containing variants are studied using a suite of high resolution characterisation techniques including atom probe tomography (APT), high resolution secondary ion mass spectroscopy (SIMS) and transmission electron microscopy (TEM). The primary effect of boron addition is the suppression of Cr-rich M23 C6 carbide and the formation instead of the Cr-rich M5 B3 boride. The SIMS analysis indicates that the boride particles are distributed fairly uniformly along the grain boundaries, of length up to 500 nm along the grain boundary. The substantial majority of the boron added resides in the form of these M5 B3 borides; some boron segregation is found at the γ ′/M5 B3 interfaces but interfaces of other forms – such as γ / γ ′, γ /M5 B3, γ /MC and γ ′/MC – show no significant segregation. Creep testing indicates that the optimum boron content in this alloy is 0.05 at.%. Graphical abstract: